Characterization of microbial communities in flavors and fragrances during storage - Feng, Yingjie; Zhang, Tingting; Yang, Jinchu; Liu, Wenzhao; Yang, Yongfeng; Huang, Jihong; Huang, Shen; Yang, Zongcan; Liu, Qianjin; Zheng, Wenchao; Zhou, Qing (Frontiers in Microbiology, 2025)
Flavors and fragrances are essential for product quality, yet they are highly susceptible to contamination due to high moisture content and rich nutrients. This study investigates microbial growth, pH changes, volatile compound dynamics, and microbial community changes during the storage of flavors and fragrances. Results indicate that total viable counts (TVC) remained stable for the first three days but increased rapidly afterward, exceeding the acceptable limit of 5 log CFU/mL by day 7. The pH levels initially rose slightly, followed by a steady decline, which indicates spoilage progression. Gas chromatography–mass spectrometry (GC–MS) analysis revealed significant degradation of key aromatic compounds, such as 5-hydroxymethylfurfural (5-HMF), vanillin, and its derivative ethyl vanillin. Whole genome shotgun (WGS) sequencing demonstrated a marked increase in microbial community richness and diversity as storage progressed, with a notable shift in composition. Early storage stages were dominated by fungal species from the Ascomycota phylum, while later stages saw a rise in spoilage-associated bacteria, particularly from the Firmicutes and Proteobacteria phyla. Throughout the storage process, Zygosaccharomyces and its dominant species, Zygosaccharomyces bailii, remained prevalent, though their average relative abundance decreased from 81.26 to 32.29%. In addition, the bacterial species Oceanobacillus sojae and Niallia nealsonii showed significant increases in relative abundance, suggesting that bacteria were one of the key contributors to the spoilage of flavors and fragrances. Functional analysis based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) database indicated a shift in metabolic pathways within the microbial community, with heightened metabolic activity correlating with spoilage. These findings provide valuable insights for improving storage methods and quality control of flavors and fragrances.